Rethinking Islamic Character Values Through Folklore and Its Implications for Strengthening Character Education Among Generation Z - Permadi, Muhammad Syafrany Surya; Hamidalloh, Ahmad Sayyidiman; Muhid, Abdul; Fahmi, Muhammad; Abdul Aziz, Faqih (Universitas Islam Negeri Ar-Raniry, 2026)
The strong development of globalization has triggered a shift in cultural values among Generation Z. Ironically, the existence of local culture as a medium for strengthening character education is slowly being eroded by the dominance of Western culture, which is oriented toward consumerist lifestyles, individualism, materialism, and hedonism, widely spread through various online platforms. This research uses a qualitative approach with Roland Barthes' semiotic analysis design. Data were obtained through observations of scenes, dialogues, and visual symbols in the film Si Sarip Tambak Oso. The data analysis process includes dialogue transcription, thematic coding, data tabulation, and meaning interpretation. Character values in the film Si Sarip Tambak Oso include: bravery, justice, social concern, resistance against tyranny, moral responsibility, steadfastness of principles, sacrifice, and exemplary behavior. The practical implication of this research is to contribute an integrative strategy for strengthening character education through the synthesis of cultural and religious values in the folklore of the film Si Sarip Tambak Oso. However, this research has limitations regarding the technical implementation of cultural character values in Islamic education. This research offers an empirical contribution by positioning folklore not merely as a cultural heritage, but as a strategic educational medium in strengthening the character of Generation Z through the synthesis of local cultural values and religious teachings amidst the challenges of globalization.